AZOSPIRILLUM BRASILENSE E VITAMINAS NA PRODUÇÃO DE ALFACE HIDROPÔNICA - LEONEL, Eduardo Augusto Souza; ARAÚJO, Thales Oliverira; SERON, Cássio de Castro; VENDRUSCOLO, Eduardo Pradi; MARTINS, Murilo Battistuzzi; JÚNNYOR, Wellingthon da Silva Guimarães (ANAIS DO ENIC, 2023)
-